PENERAPAN MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS DI SMP DWI SEJAHTERA PEKANBARU - Dian Tiara; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This research method uses the classroom action research (PTK) method. Cyclical reseach procedures. Each cycle consists of four stages including: planning, implementing action, observing, and reflecting. Data collection techniques through observation and tests. This data collection uses instruments in the form of student observation sheets and teacher performance observation sheets in the learning process, while to determine the quality of student learning outcomes used evaluation sheets or tests. Based on observation in SMP Dwi Sejahtera Pekanbaru student learning outcomes grade VIII is still low and many aims to improve the learning outcomes of social studies, through e learning models Exampl Non Example In result showed that the use of the Example non Example learning models could improve student learning outcomes in social studies subject. From the average pre cycle value of 68,86 in cycle I to 78,33 and in cycle II 82,66.Key Word: Example non Example